2022
DOI: 10.1177/10732748221103331
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Distribution of Human Papillomavirus Genotypes (1997–2019) and Their Association With Cervical Cancer and Precursor Lesions in Women From Southern Mexico

Abstract: Background Cervical cancer (CC) is the fourth most common malignancy of the female genital tract. Human Papillomavirus (HPV) is the main cause of precancerous lesions and CC cases worldwide Objective We assessed the prevalence and distribution of HPV types and their association with precancerous lesions and CC. Methods HPV genotypes were detected by 3 methods depending on the year of in which the sample was analyzed: MY09/11 RFLPs (1997 to 2010), GP5+/6+ primer systems (2005 to 2010) and INNO-LiPA HPV Genotypi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 54 publications
(99 reference statements)
1
6
0
Order By: Relevance
“…The overall prevalence of HR-HPV infection in women with precancerous lesions who were referred from first-level health centers was 69.8%, a value similar to that reported in other cross-sectional studies conducted in dysplasia clinics in some regions of Mexico (60%–90%); 28 - 32 these rates are lower than those reported in studies with regional representativeness (24.78%), 7 but they are higher than the prevalence in the open population in Mexico. 5 , 6 The prevalence of HR-HPV infection age-specific in our population is distributed as a “U-shaped” curve.…”
Section: Discussionsupporting
confidence: 84%
“…The overall prevalence of HR-HPV infection in women with precancerous lesions who were referred from first-level health centers was 69.8%, a value similar to that reported in other cross-sectional studies conducted in dysplasia clinics in some regions of Mexico (60%–90%); 28 - 32 these rates are lower than those reported in studies with regional representativeness (24.78%), 7 but they are higher than the prevalence in the open population in Mexico. 5 , 6 The prevalence of HR-HPV infection age-specific in our population is distributed as a “U-shaped” curve.…”
Section: Discussionsupporting
confidence: 84%
“…An epidemiological study of HPV infection among women in southern Mexico showed that co-infection of hrHPV genotypes of HPV-16, HPV-18, HPV-39, HPV-52, HPV-53, HPV-66, and HPV-69 with other HPV genotypes resulted in significantly higher risk of developing LSIL, HSIL, and cervical cancer. 36 Lee et al 37 also observed that subjects with multiple genotype HPV infections had a 31.8-fold higher risk of developing cervical cancer. Infection with multiple HPV genotypes can increase the risk of developing precancerous lesions, which may accelerate cancer development.…”
Section: Discussionmentioning
confidence: 96%
“…There are over 200 different HPV types. Different HPV subtypes can cause different pathological lesions, and more than 60 types of HPV are found predominantly or exclusively in the anogenital tract ( 4 ).…”
Section: Introductionmentioning
confidence: 99%